2020
DOI: 10.1002/jeab.654
|View full text |Cite
|
Sign up to set email alerts
|

Human social defeat and approach–avoidance: Escalating social‐evaluative threat and threat of aggression increases social avoidance

Abstract: Basic research on avoidance by Murray Sidman laid the foundation for advances in the classification, conceptualization and treatment of avoidance in psychological disorders. Contemporary avoidance research is explicitly translational and increasingly focused on how competing appetitive and aversive contingencies influence avoidance. In this laboratory investigation, we examined the effects of escalating social‐evaluative threat and threat of social aggression on avoidance of social interactions. During social‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In contrast, we did not find this pattern in the socially avoidant group. It seemed that socially avoidant emerging adults distributed equal attentional resources to cooperation and competition, which suggests that they might consider cooperation and competition as analogous social interactions, possibly due to their lack of social skills [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we did not find this pattern in the socially avoidant group. It seemed that socially avoidant emerging adults distributed equal attentional resources to cooperation and competition, which suggests that they might consider cooperation and competition as analogous social interactions, possibly due to their lack of social skills [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that, when dealing with necessary interpersonal interaction, socially avoidant emerging adults would feel stressed and have poor-quality relationships with others [ 3 ]. After that, they are probably unable to receive positive social evaluations from their peers, and their accumulated negative social evaluation would increase their social avoidance motivation [ 19 ]. Considering that socially avoidant emerging adults show intense social avoidance during interpersonal interaction, real interpersonal interaction would be an ideal situation to examine the ERPs related to social avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the loser learns to stay away from the area where defeat had occurred to presumably minimize the chance of encountering the aggressor 6,7 . The defeat-induced avoidance is observed across species, including humans 8 . In the US, a quarter of kids between 12-18 years old reportedly experienced bullying and showed increased social isolation and school avoidance 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have mainly focused on pathology, ignoring the social avoidance caused by disease (17). In addition, translational research on the social avoidance of human beings has been largely ignored due to difficulties in scheduling ecologically valid social threats in the laboratory (18). Therefore, paying attention to the social avoidance problems of patients with breast cancer is of significance for improving their quality of life and helping them reintegrate into society.…”
Section: Introductionmentioning
confidence: 99%